Effect of group size and maize silage dietary levels on behaviour, health, carcass and meat quality of Mediterranean buffaloes. (9th November 2015) - Masucci, F.; De Rosa, G.; Barone, C. M. A.; Napolitano, F.; Grasso, F.; Uzun, P.; Di Francia, A.
Abstract : The effects of different dietary levels of maize silage (10% v . 36% DM) and group size (7 v . 14 animals) were assessed on growth performance and in vivo digestibility of 28 male fattening buffaloes. In addition, the effects of diet on meat quality and group size on behaviour and immune response were separately evaluated. Animals were weighed and assigned to three groups. The high silage – low size group (HL) was fed a total mixed ration (TMR) containing 36% DM of maize silage and consisted of seven animals (age 12.7±2.6 months; BW 382.2±67.7 kg at the start of the study). The low silage – low size group (LL) was fed a TMR containing 10% DM of maize silage and consisted of seven animals (age 13.0±2.7 months; BW 389.4±72.3 kg). The high silage – high size group (HH) was fed the 36% maize silage DM diet and consisted of 14 animals (age 13.9±3.25 months; BW 416.5±73.9 kg). Total space allowance (3.2 indoor+3.2 outdoor m 2 /animal) was kept constant in the three groups, as well as the ratio of animals to drinkers (seven animals per water bowl) and the manger space (70 cm per animal). Growth performance, carcass characteristics and digestibility were influenced neither by dietary treatment nor by group size, even if the group fed 36% maize silage diet showed a higher fibre digestibility. No effect of diet was found on meat quality. Group size did not affect the behavioural activities with the exception of drinking (1.04±0.35% v . 2.60±0.35%; P <0.01 for groups HL and HH, respectively) and vigilance (2.58±0.46% v . 1.20±0.46%; P <0.05 for groups HL and HH, respectively). Immune responses were not affected by group size.